Computer Technician Application Design in Household Based Part (BRT) Using the SDLC Method: Computer Technician Application Design in Household Based Part (BRT) Using the SDLC Method - Fachri Muhammad; Fauziah Fauziah; Rini Rini (Jurnal Mantik, 2020)
Along with the times, technological advances also have new standards and the best servants. Currently doing repairs to facilities on campus there are still many using manual reports so that the lack of the best service for facility improvement. Making computer technician applications in the household (BRT) at Universitas Nasional can assist technicians in receiving reports quickly and practically so that technicians can immediately improve facilities, especially lab facilities at Universitas Nasional. The results of this application can make a booking and without having to take care of a complicated administration and the user can receive a notification when it has finished doing service or repairs. The application is made using platform android so it's easy and fast because everyone must use an android smartphone. By making this, it is expected to make it easier for technicians in the household section to do the work and users can easily report the damage.